2018
DOI: 10.24191/myse.v4i1.5611
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Disabled Facilities at Fi-Sabilillah Mosque, Cyberjaya

Abstract: All mosques need to be equipped with facilities for people with disabilities (PWD) in fulfilling with the requirements of the Malaysian Standard Code of Practice (MS) on Access of Disabled Persons. However, most mosques in Malaysia do not fulfil these requirements in terms of providing facilities for the PWDs. This adversely affects the PWDs to engage in the social and economic mainstream. The research aim is to classify the conformity of disabled facilities provided at Fi-Sabilillah Mosque, Cyberjaya in Selan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…According to Osman et al (2015) and Shobri et al (2018), one of the physical obstacles wheelchair users encounter at the accessible parking is a lack of space for unloading and removing them from the vehicle. Osman et al (2015) and Shobri et al (2018) asserted that among the physical barriers faced by wheelchair users at the accessible parking is insufficient space for unloading and manoeuvring them off from the car. Rahim (2021) stated that the PwD-specific parking space must be close to the main entrance, lift or toilet.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Osman et al (2015) and Shobri et al (2018), one of the physical obstacles wheelchair users encounter at the accessible parking is a lack of space for unloading and removing them from the vehicle. Osman et al (2015) and Shobri et al (2018) asserted that among the physical barriers faced by wheelchair users at the accessible parking is insufficient space for unloading and manoeuvring them off from the car. Rahim (2021) stated that the PwD-specific parking space must be close to the main entrance, lift or toilet.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The PwDs will have trouble finding their route if there is insufficient user signage at the main gate. If there is no sufficient signage for users provided at the main entrance, the PwDs will find difficulties finding their way in the building (Shobri et al, 2018;Rahim et al, 2015). The display screen provided should not have shading and glare that make the screen unclear.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…In the same country, Shobri, Zakaria, and Salleh also used a checklist and found that lack of finances and awareness led to the non-provision of accessibility means in the studied mosque. Another important reason was the local authority's lack of law enforcement [18]. Abd Samad, Rahim, and Said used an access audit checklist derived from Malaysian standards to evaluate accessibility in a different Malaysian mosque.…”
Section: Pwds' Accessibility At Mosquesmentioning
confidence: 99%
“…Meanwhile, Shobri et al (2018) have claimed that accessible design only benefits the PWD. Individuals with multiple disabilities have distinct accommodation, support and facility requirements from the general population.…”
Section: Accessibility Of Design Elements In Housingmentioning
confidence: 99%